(untitled) (CIPEEX, 2025)
Tooth loss, defined as the partial or total absence of teeth, represents a condition that affects not only aesthetics and masticatory function but also the physical and psychological health of individuals. Its occurrence goes beyond biological causes, being strongly associated with factors such as inadequate oral hygiene, limited access to dental care, low educational level, and reduced household income. This study consists of a literature review. The bibliographic search was conducted between March and August 2025 in databases including PubMed, SciELO, LILACS, and Google Scholar. The descriptors “Tooth loss,” “Mastication,” “Speech,” and “Quality of life” were used in Portuguese, English, and Spanish. The reviewed literature shows that tooth loss compromises mastication, leading to overload of the remaining teeth and difficulties in food grinding, which may result in nutritional deficiencies. Speech is also impaired, particularly in the articulation of phonemes such as /f/, /s/, and /v/, which affects the clarity of communication. From a psychosocial perspective, tooth loss is associated with reduced self-esteem, embarrassment in social interactions, and a tendency toward isolation. Tooth loss transcends the aesthetic dimension, impairing essential functions such as mastication and speech, while negatively impacting emotional and social well-being. Early tooth replacement, combined with preventive strategies and oral health education, is indispensable for restoring oral function and improving quality of life. Therefore, the role of the dental surgeon should not be limited to rehabilitation but should also focus on the promotion and maintenance of oral health.